“Life in Plastic, but Patriarchy isn’t Fantastic”: Barbie (2023) as a Confrontation of Gender Inequality - Jacklyn Meiliana Alifia; Ellita Permata Widjayanti; Muhammad Dirgantara Esa Valentino Am (Pusat Studi Gender Universitas Jember, 2026)
This study explores how Barbie (2023), directed by Greta Gerwig, critiques gender inequality and the persistence of patriarchal values through its story and imagery. By applying Laura Mulvey’s concept of the male gaze and Sylvia Walby’s framework of patriarchal structures, the research investigates how the film reconstructs ideas of femininity and masculinity. Using a qualitative descriptive approach, the analysis focuses on dialogue, visual framing, and narrative structure across both Barbie Land and the real world. The findings reveal that the film questions objectification and rigid gender norms, expressing a feminist message that values independence, emotional depth, and self-awareness. This study also highlights how popular cinema can act as a medium for challenging patriarchal narratives and supporting feminist perspectives within mass culture.